Low dose Aspirin in Prevention of Pre Eclampsia A Randomized Controlled Trial in BIRDEM-2 General Hospital - Khatun, Shapla; Begum, Ferdousi (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Objective: To assess the efficacy and safety of prophylactic low-dose aspirin (75 mg daily) started at 12–19 weeks of gestation for preventing preeclampsia in high-risk pregnant women in Bangladesh. Methods: In this open-label randomized controlled trial, 200 high-risk women were allocated 1:1 to aspirin (n = 100) or standard care (n = 100) at BIRDEM-2 Hospital, Dhaka. Aspirin was continued until 36 weeks or delivery. The primary outcome was preeclampsia (blood pressure ≥140/90 mmHg with proteinuria ≥2+). Secondary outcomes included blood pressure, proteinuria, gestational age at onset, and maternal–fetal outcomes. Analyses followed the intention-to treat principle. Ethical clearance was obtained from IRB and the trial was registered. Results: Baseline characteristics were comparable. Preeclampsia occurred in 8% of aspirin users versus 48% of controls (relative risk 0.22, 95% CI 0.12–0.43; p = 0.001). Mean systolic and diastolic pressures at delivery were lower by 19.9 mmHg and 11.4 mmHg, respectively (both p = 0.001). Significant proteinuria (e”2+) was observed in 6% versus 46% (RR 0.44; 95% CI 0.31–0.61). Gestational hypertension declined non-significantly (21% vs 31%). Maternal and fetal complications, including preterm birth, low birth weight, and NICU admission, did not differ between groups. Conclusions: Prophylactic low-dose aspirin initiated early in pregnancy reduced preeclampsia risk by 78% without adverse effects, demonstrating a safe, low-cost preventive strategy for high-risk women in resource-limited settings. Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 101-114